2012
DOI: 10.12741/ebrasilis.v5i2.200
|View full text |Cite
|
Sign up to set email alerts
|

Borboletas e Mariposas (Insecta: Lepidoptera) do Município de Joaçaba, Estado de Santa Catarina, Brasil

Abstract: Resumo. Pela primeira vez é apresentada uma lista de Lepidoptera registrados no município de Joaçaba, estado de Santa Catarina, Brasil. Os indivíduos foram coletados entre os anos de 2006 e 2010 em diferentes ambientes resultando em 58 espécies pertencentes a dez famílias. As famílias mais abundantes foram Nymphalidae e Saturniidae, representando 34,48% e 24,13% da riqueza de espécies respectivamente. Além disso, os gêneros mais representativos de Nymphalidae foram Morpho (três espécies) e Hamadryas (duas espé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
1
1
Order By: Relevance
“…The present study showed greater richness of species than the studies performed by Santana (2005), Rosa et al (2011), Pedrotti et al (2011), Favretto (2012), Ramos Soares et al (2012). However, compared with records for several Brazilian states such as recorded by Isehard and Romanowski (2004), Marchiori and Romanowski (2006), Emery et al (2006), Dessuy and Morais (2007), Pinheiro et al (2008), Isehard et al (2010), Ritter et al (2011), Zacca and Bravo (2012), and Bogiani et al (2012), the number of species found is lower.…”
Section: Discussioncontrasting
confidence: 56%
“…The present study showed greater richness of species than the studies performed by Santana (2005), Rosa et al (2011), Pedrotti et al (2011), Favretto (2012), Ramos Soares et al (2012). However, compared with records for several Brazilian states such as recorded by Isehard and Romanowski (2004), Marchiori and Romanowski (2006), Emery et al (2006), Dessuy and Morais (2007), Pinheiro et al (2008), Isehard et al (2010), Ritter et al (2011), Zacca and Bravo (2012), and Bogiani et al (2012), the number of species found is lower.…”
Section: Discussioncontrasting
confidence: 56%
“…Para avifauna: Accordi & Barcellos (2008), Favretto & Guzzi (2008), Favretto et al (2008), Favretto & Geuster (2008a, 2008b), Favretto & Santos (2009), Favretto et al (2010), Favretto & Geuster (2011), Favretto & Guzzi (2011, Jesus & Marafon (2014), Favretto (2015a, Rosário (2016) e WikiAves (2015. Para mastofauna: Cherem et al (2007), Onghero-Jr. (2008), Padilha (2011), Favretto & Onghero-Jr. (2011), Engera (2013), Fachini & D'Agostini (2013, Santos & Marafon (2013), Biassi (2014), Neres (2015) e consulta ao SpeciesLink (2016) para dados da Coleção Zoológica de Referência da Seção de Vírus Transmitidos por Artrópodos (IAL-roedores).…”
Section: Métodosunclassified
“…In the western region of the Santa Catarina state, southern Brazil, for instance, there are many studies related to insects (SILVA, 1999;SILVA & SILVESTRE, 2000;SILVA & SILVESTRE, 2004;LUTINSKI & GARCIA, 2005;GRACIANI et al, 2005;MARCONDES et al, 2006;RAVANELLO, 2007;LUTINSKI et al, 2008;IOP et al, 2009;BATTISTONI, 2012;FAVRETTO, 2012;SCHMIDT et al, 2012;SANTOS et al, 2013;FAVRETTO et al, 2013a;FAVRETTO et al, 2013b;RAIMUNDI et al, 2013;FAVRETTO et al, 2014;SANTOS et al, 2014;FAVRETTO et al, 2015;ORLANDIN et al 2017). However, only Ravanello's research (2007) covers the entire extension of hydrographic basins as sampling parcels, as the other papers have focus on forest remnants, small areas or dispersal species record.…”
Section: Introductionmentioning
confidence: 99%